KINERJA PEGAWAI DALAM MEMBERIKAN PELAYANAN KESEHATAN PADA PASIEN GANGGUAN JIWA DI RUMAH SAKIT JIWA PROVINSI SULAWESI TENGGARA - Mila, Wa; Justawan, H.; Manguntara, La (REZ PUBLICA, 2020)
This research is a descriptive qualitative study, as many as five informants in this study. Data collection techniques are direct observation and direct interviews. As for the data analysis used data reduction, data presentation, draw conclusions.The results of this study indicate that the performance of employees in providing services to mental patients in the Southeast Sulawesi Provincial Mental Hospital can be quite good. Said to be quite good because of the 4 indicators of performance achievementÂ  (quality, quantity, timeliness, an work commitment) only 1 indicator that is fully in line with community expectations, namely the quality indicator. While the indicators of quality, timeliness, and work commitment are still said to be poor because there are still complaints from the community. While the quality of health services in the Mental Hospital of Southeast Sulawesi Province is included in the good category. Becauce of the 5 aspects of service quality (physical appearance, responsiveness, reliability, assurance, and empathy)Â  only 1 indicator does not meet the expectations of the community, namely the asspect of physical appearance.